Implementing Strategic Management for Learning Quality: How Rural School Principals Navigate Resource Constraints - Nurhalizah Nurhalizah; Rizal Rizal; Surahman Wilade; Nashrullah Nashrullah; Dyah Aini Purbarani; Sisriawan Lapasere (Journal of Innovation and Research in Primary Education, 2026)
Primary education plays a critical role in shaping future human resources, making the quality of learning processes essential. This study examined the strategic management practices of the principal at SDN 2 Bora, a rural primary school in Indonesia, in achieving national learning process standards. The research addressed challenges commonly faced by rural schools, including limited facilities, varied teacher competencies, and fluctuating student motivation. A qualitative case study design was employed, involving 16 teachers, 150 students, 30 parents, and educational staff as participants. Data were collected through questionnaires, systematic observations, in-depth interviews, and document analysis. The Miles and Huberman interactive model was used for data analysis, supplemented by triangulation techniques to ensure trustworthiness. Findings revealed that the principal demonstrated effective strategic management across three key components. Strategic planning was conducted collaboratively and systematically (teacher rating: 95.0%, student: 87.6%, parent: 94.6%). Implementation was supported through active instructional leadership and supportive supervision (teacher: 92.5%, student: 88.5%, parent: 86.8%). Evaluation was performed regularly to guide continuous improvement (teacher: 90.9%, student: 89.3%, parent: 87.1%). Overall stakeholder satisfaction averaged 90.2%, categorized as "Very Good." The study concludes that strategic management significantly improved teacher performance, student engagement, and parental involvement, demonstrating that effective leadership can overcome resource constraints in achieving educational quality standards in rural primary schools.